Career choices in dermatology. - Clayton, R; Lambert, T; Burge, S (2010)
Reforms to both undergraduate and postgraduate training have resulted in limited exposure to clinical dermatology, and therefore we need to target advice and clinical attachments to the most appropriate stages of training to ensure that dermatology is considered as a career option by medical students. A questionnaire survey was undertaken to determine when and how doctors chose their career in dermatology. An electronic questionnaire was sent to 709 dermatologists (response rate 44%). Of the respondents, 49% considered dermatology after medical school attachment and 61% were influenced by the jobs they had done as a pre-registration house officer (PRHO) or senior house officer (SHO). Careers advice was lacking, with only 11% receiving it while at medical school and 29% during their PRHO/SHO years. Contact with an inspiring clinician was the most influential factor in choosing dermatology. Both medical students and junior doctors, should have opportunities to learn from and work with clinical dermatologists.